Electrical Loss Management by Molecularly Manipulating Dopant‐free Poly(3‐hexylthiophene) towards 16.93 % CsPbI2Br Solar Cells - Li, Ming‐Hua; Shao, Jiang‐Yang; Jiang, Yan; Qiu, Fa‐Zheng; Wang, Shuo; Zhang, Jianqi; Han, Guangchao; Tang, Jilin; Wang, Fuyi; Wei, Zhixiang; Yi, Yuanping; Zhong, Yu‐Wu; et al. (Angewandte Chemie International Edition, 2021)
Inorganic cesium lead halide perovskites offer a pathway towards thermally stable photovoltaics. However, moisture‐induced phase degradation restricts the application of hole transport layers (HTLs) with hygroscopic dopants. Dopant‐free HTLs fail to realize efficient photovoltaics due to severe electrical loss. Herein, we developed an electrical loss management strategy by manipulating poly(3‐hexylthiophene) with a small molecule, i.e., SMe‐TATPyr. The developed P3HT/SMe‐TATPyr HTL shows a three‐time increase of carrier mobility owing to breaking the long‐range ordering of “edge‐on” P3HT and inducing the formation of “face‐on” clusters, over 50 % decrease of the perovskite surface defect density, and a reduced voltage loss at the perovskite/HTL interface because of favorable energy level alignment. The CsPbI2Br perovskite solar cell demonstrates a record‐high efficiency of 16.93 % for dopant‐free HTL, and superior moisture and thermal stability by maintaining 96 % efficiency at low‐humidity condition (10–25 % R. H.) for 1500 hours and over 95 % efficiency after annealing at 85 °C for 1000 hours. An electrical loss management strategy by using SMe‐TATPyr molecule manipulating dopant‐free Poly(3‐hexylthiophene) (P3HT) has been developed and employed to fabricate efficient and thermally stable CsPbI2Br solar cells. The P3HT/SMe‐TATPyr presents optimized molecular orientation, favorable energy level alignment and effective defect passivation. Based on P3HT/SMe‐TATPyr HTLs, the fabricated devices yield a record‐high efficiency of 16.93 % for CsPbI2Br solar cells with dopant‐free HTLs.